A Chain‐Based 2 D Cobalt(II) Coordination Polymer with a "Crab‐Like" Flexible Dicarboxylate Ligand: A Weak Ferromagnetic Single‐Chain Magnet. Issue 9 (5th July 2013) - Zhang, Qingfu; Zhang, Haina; Zeng, Suyuan; Sun, Dezhi; Zhang, Chong
<x xml:space="preserve">Abstract</x> Chain gang: A chain‐based 2D CoII coordination polymer was prepared by hydrothermal reaction of Co(NO3)2⋅6 H2O, H2L and bpa in the presence of sodium hydroxide. Magnetic investigation revealed canted antiferromagnetism, magnetic hysteresis, and slow magnetic relaxation. Thus, this complex could be considered as a new homospin weak ferromagnetic single‐chain magnet.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>